2019
DOI: 10.1155/2019/5852494
|View full text |Cite
|
Sign up to set email alerts
|

Antiobesity, Regulation of Lipid Metabolism, and Attenuation of Liver Oxidative Stress Effects of Hydroxy-α-sanshool Isolated from Zanthoxylum bungeanum on High-Fat Diet-Induced Hyperlipidemic Rats

Abstract: Zanthoxylum bungeanum is a traditional Chinese medicine (TCM) used to relieve pain, dispel dampness, stop diarrhea, and prevent itching. The aim of this study was to investigate the antiobesity and hypolipidemic effects of hydroxy-α-sanshool (HAS) isolated from Z. bungeanum on hyperlipidemic rats. Wistar rats (n=48) were randomly divided into six groups: (1) normal diet rats (ND), (2) high-fat diet- (HFD-) treated rats, (3) HFD+fenofibrate-treated rats (HFD+FNB), (4) HFD+low dose of HAS-treated rats (HFD+LD, 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 23 publications
4
36
0
1
Order By: Relevance
“…Moreover, the activity of the citrate synthase enzyme was measured, at the level of the visceral adipose tissue, as a marker of the metabolic activity of adipocytes ( Figure 5). As previously described in literature, the HFD significantly reduced the activity of citrate synthase [57], while the addition of EVOO brought it back to standard levels. The addition of CaOO and ClOO increased the average activity of this enzyme but less markedly than CEVOO ( Figure 5).…”
Section: Effects Of Cevoo Caoo and Cloo Supplementation On Cardiometsupporting
confidence: 78%
See 2 more Smart Citations
“…Moreover, the activity of the citrate synthase enzyme was measured, at the level of the visceral adipose tissue, as a marker of the metabolic activity of adipocytes ( Figure 5). As previously described in literature, the HFD significantly reduced the activity of citrate synthase [57], while the addition of EVOO brought it back to standard levels. The addition of CaOO and ClOO increased the average activity of this enzyme but less markedly than CEVOO ( Figure 5).…”
Section: Effects Of Cevoo Caoo and Cloo Supplementation On Cardiometsupporting
confidence: 78%
“…Further, as described in literature, the HFD significantly reduced the activity of citrate synthase enzyme [57], while the addition of CEVOO brought it back to standard levels. CaOO and ClOO, although less markedly, increased the average activity of this enzyme.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…2004 ; Wang et al. 2019 ). In our results, it’s interesting that QMY treatment could decrease the levels of TC, TG and LDL in serum of ASO rabbit.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that ZA have a significant effect on the lipid metabolism in hyperlipidemia rats (Lv, 2014;Wang et al, 2019), nerve stimulation (Kuroki, Hagura, Nishida, Haggard, & Watanabe, 2016), the improvement of T1DM (Ren, 2017), the shortterm amelioration of skin conditions (Hao et al, 2019), cruor (Yang et al, 2014), narcosis (Tarus, Coombes, Crouch, & Mulholland, 2006), and so on. Additionally, like the stictic acid, ZA can also promote colonic peristalsis (Hiraishi et al, 2018;Kubota et al, 2019;Pejin, Iodice, Bogdanovic, Kojic, & Tesevic, 2017).…”
Section: Introductionmentioning
confidence: 99%